Analisis Tata Kelola Seleksi Partai Politik Peserta Pemilu 2024: Studi Empiris di Kota Medan - Saddam Lubis; Matius Bangun; Mhd. Ansori Lubis (Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
This study analyzes the governance of political party selection for the 2024 General Election in Medan City from the perspective of Good Electoral Governance. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observation, and documentation involving election administrators, election supervisors, political parties, academics, and civil society organizations. The data were analyzed using the interactive model developed by Miles, Huberman, and Saldaña. The findings indicate that the governance of political party selection has generally been implemented well, particularly in terms of legal certainty and effectiveness. Transparency and accountability have been applied through information systems and verification mechanisms; however, technical issues in the Political Party Information System (SIPOL) remain a challenge. In addition, public participation is still relatively low. These findings suggest that the implementation of Good Electoral Governance still faces challenges, particularly in terms of participation and substantive transparency. The study concludes that strengthening public participation and optimizing information systems are necessary to improve the quality of political party selection governance.